A novel color edge detection algorithm in RGB color space - Xin Chen; Houjin Chen (IEEE 10th INTERNATIONAL CONFERENCE ON SIGNAL PROCESSING PROCEEDINGS, 2010)
Since edge indicates the outline of an object and also can provides important information to separate the objects from the background or other overlapping objects, edge detection is an essential tool in image processing and computer vision. Compared with gray image, color image provides more edge information of objects. However, the current color edge detection algorithms acquired so much time to compute and they are hardly used in real-time system. In order to improve the efficiency and the performance of the color edge detection, a novel color edge detection algorithm is proposed in this paper. In the propose algorithm, an improved Kuwahara filter is used to smooth the original image first. After edge detection with each channel independently in RGB color space, an adaptive threshold selection method is applied to predict the optimum threshold value and an edge thinning algorithm is used to extract accurate edge. The proposed algorithm is applied to a lots of color images and the result show that the algorithm works well with color images in different situation and it can be used in certain realtime system too.